Should Hospitals Return User Fees to Treasury? - Piatti-Funfkirchen, Moritz; Hashim, Ali; Yoo, Katelyn (World Bank, Washington, DC, 2020)
Charging user fees at point of service delivery has been widely debated, but much less so how user fees should be managed. User fees constitute a financial barrier and can inhibit critical access to service delivery, especially for the poor and vulnerable. This policy note recognizes that many hospitals still charge for service provision at point of use. The policy note addresses the question on whether the funds collected should be retained at the facility, which stands in contrast to the public finance laws of many countries.